Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1042/cs20120233
|View full text |Cite
|
Sign up to set email alerts
|

Substrates of Factor XIII-A: roles in thrombosis and wound healing

Abstract: FXIII (Factor XIII) is a Ca²+-dependent enzyme which forms covalent ϵ-(γ-glutamyl)lysine cross-links between the γ-carboxy-amine group of a glutamine residue and the ϵ-amino group of a lysine residue. FXIII was originally identified as a protein involved in fibrin clot stabilization; however, additional extracellular and intracellular roles for FXIII have been identified which influence thrombus resolution and tissue repair. The present review discusses the substrates of FXIIIa (activated FXIII) involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 144 publications
1
85
0
1
Order By: Relevance
“…Fibronectin, an extracellular matrix protein involved in cell adhesion and migration, is cross-linked to fibrin -chains by FXIIIa, via its glutamine residues 3, 4 and 16 [37], although no lysine residue donors have yet been identified in fibrin. Cross-linking of fibronectin to fibrin has been shown to have no effect on clot rigidity, however those clots were denser, with smaller pores [37].…”
Section: Other Cross-linking To Fibrinmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibronectin, an extracellular matrix protein involved in cell adhesion and migration, is cross-linked to fibrin -chains by FXIIIa, via its glutamine residues 3, 4 and 16 [37], although no lysine residue donors have yet been identified in fibrin. Cross-linking of fibronectin to fibrin has been shown to have no effect on clot rigidity, however those clots were denser, with smaller pores [37].…”
Section: Other Cross-linking To Fibrinmentioning
confidence: 99%
“…Cross-linking of fibronectin to fibrin has been shown to have no effect on clot rigidity, however those clots were denser, with smaller pores [37]. A more recent study by Ramanathan et al, in a purified system in the absence of FXIII, showed that fibronectin increases the initial rate of fibrin polymerisation, leading to the formation of denser clots [38], thought to be more resistant to fibrinolysis [39].…”
Section: Other Cross-linking To Fibrinmentioning
confidence: 99%
“…The detailed molecular mechanisms of the role that FXIIIa plays in this process have recently been reviewed. 21 Interestingly, recent evidence suggests that the release kinetics of fibrinopeptides is different between soluble and surface bound fibrinogen, with FpB being released at a higher rate than FpA from the surface bound configuration. 20 This may have important functional consequences in vivo because the FpB is a known chemoattractant for neutrophils and fibroblasts in vitro.…”
Section: Hemostasismentioning
confidence: 99%
“…However, there is a possibility of side effects and complications including back pain, radiculopathy, meningitis, and rebound intracranial hypertension (9). Coagulation factor XIII is well known as a clot-stabilizing factor and circulates in the blood in the form of a proenzyme (4,10). Thrombin and Ca 2+ convert Factor XIII to its active form.…”
Section: Introductionmentioning
confidence: 99%